2021
DOI: 10.3390/nu13061740
|View full text |Cite
|
Sign up to set email alerts
|

High Fat Activates O-GlcNAcylation and Affects AMPK/ACC Pathway to Regulate Lipid Metabolism

Abstract: A high-fat diet often leads to excessive fat deposition and adversely affects the organism. However, the mechanism of liver fat deposition induced by high fat is still unclear. Therefore, this study aimed at acetyl-CoA carboxylase (ACC) to explore the mechanism of excessive liver deposition induced by high fat. In the present study, the ORF of ACC1 and ACC2 were cloned and characterized. Meanwhile, the mRNA and protein of ACC1 and ACC2 were increased in liver fed with a high-fat diet (HFD) or in hepatocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…Previous investigations of the link between O‐GlcNAcylation and fatty acid metabolism have largely focused on upstream pathways including AMPK and mTORC1 signalling, as well as transcriptional regulation of FASN through the regulation of transcription factors and FASN stability [38,41–43]. In particular, transcription factors such as carbohydrate‐responsive element‐binding protein (ChREBP) and sterol regulatory element‐binding protein 1c (SREBP1c) have been reported to be activated by O‐GlcNAcylation, thereby enhancing FASN expression [41,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of the link between O‐GlcNAcylation and fatty acid metabolism have largely focused on upstream pathways including AMPK and mTORC1 signalling, as well as transcriptional regulation of FASN through the regulation of transcription factors and FASN stability [38,41–43]. In particular, transcription factors such as carbohydrate‐responsive element‐binding protein (ChREBP) and sterol regulatory element‐binding protein 1c (SREBP1c) have been reported to be activated by O‐GlcNAcylation, thereby enhancing FASN expression [41,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…The TG content was analyzed according to a previous study (20). After TM treatment for 12 h, cells were incubated with BODIPY 493/503 (Sigma) for 10 min, washed with phosphate buffer solution (PBS, Solarbio) three times, and then immediately observed lipid droplets in the cells with a fluorescent microscope (Nikon, Japan), according to the methods in a previous study (21).…”
Section: Tg Content and Lipid Droplet Stainingmentioning
confidence: 99%
“…By contrast, PA led to a 50% decrease in the O- GlcNAcylation of SHSY-5Y human neuroblastoma cells, mimicking the similar effect of HFD on the hippocampus ( 12 ). Oleate (OA), an endogenously abundant unsaturated LCFA, was reported to drive protein O- GlcNAcylation in primary hepatocytes from fish ( 31 ) and rat neonatal cardiomyocytes ( 32 ). Importantly, LCFA concentrations in these experiments, 100-600 uM PA or 400-800 uM OA, were within the physiological range for human plasma ( 33 ) although the durations of exposure varied widely by experiment, from 2 to 48 hours (see Supplementary Table S1 for study details).…”
Section: Lipid Influence On the O- Glcnac Regulato...mentioning
confidence: 99%
“…Data from in vitro experiments is more preliminary but suggests that lipid regulation of OGT and OGA is less direct than for F6P and HBP enzymes. Two studies found increased OGT/ogt mRNA following LCFA exposures – with PA in human gastric cancer cells ( 28 ) or OA in primary hepatocytes from yellow croaker fish ( 31 ). However, PA in mouse liver and macrophage cells had no effect on transcription of Ogt or Oga ( 25 , 26 ).…”
Section: Lipid Influence On the O- Glcnac Regulato...mentioning
confidence: 99%